PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MASA PANDEMI COVID 19 (STUDI KASUS PADA BISNIS RITEL PAKAIAN “STING” CABANG KEDOYA GREEN GARDEN) - Rohmanuddin Rohmanuddin; Hana Arif Suprayogo (STIE Wiyatamandala, 2022)
This research was made with the aim of knowing the influence between brand image and price, either partially or simultaneously on purchasing decision during the covid 19 periode, with a case study of the clothing retail business “Sting” Kedoya branch, Green Garden. In this study, the author uses a sampling technique that is sampling purpose. Where the author takes the research sample, namely the community in the RT 06 area, North Kedoya village, West Jakarta as many as 170 people. The instrument in this study used a questionnaire which was then processed using the IBM SPSS version 25.0 application software followed by multiple linear regression analysis. The result of this study indicate that simultaneously the brand image (X1) and price (X2) variables have a significant and positive effect on purchasing decisions (However, partially the brand image (X1) variable does not have a positive influence on purchasing decisions, and only the price variable (X2) which has a positive influence on purchasing decisions (Y). The results on the coefficient test of determination (R) show that the influence of brand image (X1) and price (X2) variables has an influence of 0.908 or 90.8% on purchasing decisions (Y). Meanwhile, 9.29% is influenced by other variables outside of this research.